Worlds Apart: a comparative analysis of discourses of English in the curricula of England and Australia - Gardner, Paul (2017)
A comparative analysis of English in the primary curricula of England and Australia reveals markedly different policy perspectives of the functions and purposes of language, literacy and literature in these two Anglophone countries. Whilst the Australian curriculum incorporates ‘the basics’ with broader socio-linguistic views of language in an attempt to construct breadth and balance, the English curriculum is predominantly a didactic adherence to ‘the old basics’. Using discourse and content analysis, a systematic review of the two curricula is undertaken and evaluated by applying Cox's five models of English and Kalantzis et al.'s four paradigms of literacy. The results of this study have important implications for teachers, academics and policy-makers in all Anglophone countries, especially the two countries that are the focus of the study.